Dermaptera Community Structure on Oil Palm Ecosystem in Dharmasraya District, Indonesia: Struktur Komunitas Dermaptera pada Ekosistem Kelapa Sawit di Kabupaten Dharmasraya, Indonesia - Munzir Busnia; Irwin Mirza Umami; Marina (Jurusan Budidaya Perkebunan, 2024)
The oil palm ecosystem is one of the suitable habitats for the order Dermaptera. Several physical factors, especially humidity in the oil palm ecosystem, support these insects' existence. In the oil palm ecosystem, Dermaptera has several functions, including as a predator of oil palm pests, but on the other hand, these insects also prey on Elaeidobius kamerunicus Faust, the primary pollinator of oil palm plants. For that reason, research was conducted to study the structure of the Dermaptera community in the ecosystem of oil palm plantations in the Sitiung sub-district. This research was a survey conducted at three locations- Sitiung, Gunung Medan, and Sungai Duo Villages—the collection of insect samples by hand collection. Identification of insect samples was carried out at the species level according to Burr (1910) and Borror et al. (1996). In this study, 214 individuals of the order Dermaptera were found to consist of three species: Cheslisoches mario, Forficula auricularia, and Vostox brunneipennis. C. mario was the dominant Dermaptera species found with an Importance Value Index (IVI) was 1.27. Based on this research, it is known that the community structure of the order Dermaptera was simple because it has low diversity values.